2022
DOI: 10.1021/acsenergylett.2c02148
|View full text |Cite
|
Sign up to set email alerts
|

Additive Engineering with Triple Cations and Bifunctional Sulfamic Acid for Tin Perovskite Solar Cells Attaining a PCE Value of 12.5% without Hysteresis

Abstract: Imidazolium (IM) and cesium (Cs) were treated as A-site cationic additives for a triiodide tin perovskite solar cell (FASnI 3 ; FA, formamidinium) with sulfamic acid (SA) as a bifunctional additive in varied proportions. IM has a tight aromatic structure that is feasible to passivate the crystal defects and help in perovskite crystallization. Cs can stabilize the crystal structure and decrease trap state densities. TOF-SIMS measurements show the passivation effect of both IM and SA occurring on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Numerous works have been devoted to enhancing the crystal quality of THPs by controlling the crystallization processes of THP films. For instance, Hao et al revealed that an intermediate solvate SnI 2 ·3DMSO could form to reduce the crystal growth rate of THPs when dimethyl sulfoxide (DMSO) was chosen as the solvent of a THP precursor solution . Jokar et al reported that the nucleation sites of THPs increased after introducing EDAI 2 in the FASnI 3 (FA: formamidinium) film, resulting in uniform and dense THP films .…”
mentioning
confidence: 99%
“…Numerous works have been devoted to enhancing the crystal quality of THPs by controlling the crystallization processes of THP films. For instance, Hao et al revealed that an intermediate solvate SnI 2 ·3DMSO could form to reduce the crystal growth rate of THPs when dimethyl sulfoxide (DMSO) was chosen as the solvent of a THP precursor solution . Jokar et al reported that the nucleation sites of THPs increased after introducing EDAI 2 in the FASnI 3 (FA: formamidinium) film, resulting in uniform and dense THP films .…”
mentioning
confidence: 99%
“… Crystal structure. The crystal structure plays a critical role in stabilizing tin perovskite, as it affects the defect formation energy and band alignment. ,,, Mixing different cations in the perovskite structure has been shown to decrease the crystal strain and increase the defect formation energy, leading to improved stability. ,, Recent studies have demonstrated that adding larger organic cations, such as guanidinium, , azetidinium, or imidazolium, to the perovskite precursor solution can enhance the stability and increase the defect formation energy. Introducing bulky organic cations with heteroatoms can also affect the crystal formation energy, leading to improved stability.…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made to control the crystallization process of RP tin-based perovskites via additives, 12–14 solvents, 15,16 and composition engineering. 17,18 For example, poly(4-vinylphenol) and poly(vinyl pyrrolidone) were employed to increase nucleation sites, improving the morphology and crystallization of RP tin-based perovskite films.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Currently, the highest reported photovoltaic efficiency based on 2D RP tin halide perovskite (n = 4) is 10.36%, 10 far lower than its Shockley-Queisser limit value (∼32%). 11 Several efforts have been made to control the crystallization process of RP tin-based perovskites via additives, [12][13][14] solvents, 15,16 and composition engineering. 17,18 For example, poly (4vinylphenol) and poly(vinyl pyrrolidone) were employed to increase nucleation sites, improving the morphology and crystallization of RP tin-based perovskite lms.…”
Section: Introductionmentioning
confidence: 99%